Family Caregiving Burden in Romantic Relationships: A Relational Turbulence Theory Analysis. Issue 4 (4th July 2021) - Bevan, Jennifer L.; Ball, Hannah; Urbanovich, Tessa; Craw, Erin
ABSTRACT: In addition to health and financial burdens, family caregivers can experience stress in their romantic relationships. Relational turbulence theory (RTT) is used to understand how family caregivers and caregivers' romantic partners navigate relational transitions and caregiver burden when one partner is providing informal care to another aging family member. Three hundred and nineteen participants, who were either the romantic partner providing care or the romantic partner of a family caregiver, completed an online survey. Tests of RTT and caregiver burden revealed that relational uncertainty, partner facilitation, and relational turbulence were related to caregiver burden as predicted for family caregivers; relational uncertainty was unrelated to caregiver burden for romantic partners. Partner interference was unrelated to caregiver burden. Theoretical and practical implications are discussed. Abstract :